Bridging Data and Decisions 2014
DOI: 10.1287/educ.2014.0129
|View full text |Cite
|
Sign up to set email alerts
|

Research in Public Health for Efficient, Effective, and Equitable Outcomes

Abstract: Public health focuses on preventing disease, prolonging life, and promoting health in a population, and there are many ways in which operations research and management science (OR/MS) researchers can contribute to improved decision making in this area. In this tutorial, we discuss examples of work in several areas of public health, including access and equity, disease screening, chronic diseases, and infectious diseases. In each of these areas, we give a brief overview of challenging issues and related literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Non-communicable diseases such as diabetes and heart disease make up a significant portion of the burden of disease in the world (Ayer et al, 2014 ; Gakidou et al, 2017 ). The COVID-19 pandemic showed that they also induce severe complications when such communicable diseases strike (Guo et al, 2020 ; Khan et al, 2020 ).…”
Section: The Casementioning
confidence: 99%
“…Non-communicable diseases such as diabetes and heart disease make up a significant portion of the burden of disease in the world (Ayer et al, 2014 ; Gakidou et al, 2017 ). The COVID-19 pandemic showed that they also induce severe complications when such communicable diseases strike (Guo et al, 2020 ; Khan et al, 2020 ).…”
Section: The Casementioning
confidence: 99%
“…Because of the complexity of the health care systems, 95 intervening to improve access requires system-specific considerations, including different constraints in supply and demand for treatment and prevention, for example, varying prevalence of at-risk or affected populations across communities, limited treatment or vaccine availability, preferences and behaviors depending on demographics, and limited participation of specialized health care providers in public insurance programs. Accounting for such constraints in access to prevention and treatment is critical to reducing the potential health disparities arising owing to the severe health outcomes in epidemics.…”
Section: Prediction Of and Responding To Disease Spread During An Infmentioning
confidence: 99%
“…Screening of asymptomatic individuals (possibly followed with a diagnostic procedure, depending on screening results) can diagnose disease at earlier stages and increase the chances of treatment success (Ayer et al 2014). Although screening benefits a small percentage of the population who have the disease, it is costly, and the majority of the remaining population receives little or no direct benefit, and may even be exposed to physical or emotional harms.…”
Section: Medical Decision Makingmentioning
confidence: 99%
“…To continue on the path of improving population health, we must strive to widen access (e.g., by improving availability of vaccines and reducing waiting times), improve efficiency and quality of care (e.g., by increasing quality-adjusted life years while minimizing costs), and promote equity (e.g., ensure that access and outcomes are comparable across different geographical areas, demographic groups, income levels, etc.) (Ayer et al 2014). Achieving these improvements is, to a large extent, an operational challenge; these improvements can only be achieved by identifying more efficient ways of organizing and delivering care (Green 2012).…”
Section: Introductionmentioning
confidence: 99%